Synthetic Biology Makes Polymer Materials Count. Issue 21 (30th March 2018) - Beyer, Hannes M.; Engesser, Raphael; Hörner, Maximilian; Koschmieder, Julian; Beyer, Peter; Timmer, Jens; Zurbriggen, Matias D.; Weber, Wilfried
Abstract: Synthetic biology applies engineering concepts to build cellular systems that perceive and process information. This is achieved by assembling genetic modules according to engineering design principles. Recent advance in the field has contributed optogenetic switches for controlling diverse biological functions in response to light. Here, the concept is introduced to apply synthetic biology switches and design principles for the synthesis of multi‐input‐processing materials. This is exemplified by the synthesis of a materials system that counts light pulses. Guided by a quantitative mathematical model, functional synthetic biology‐derived modules are combined into a polymer framework resulting in a biohybrid materials system that releases distinct output molecules specific to the number of input light pulses detected. Further demonstration of modular extension yields a light pulse‐counting materials system to sequentially release different enzymes catalyzing a multistep biochemical reaction. The resulting smart materials systems can provide novel solutions as integrated sensors and actuators with broad perspectives in fundamental and applied research. Abstract : How to count on biomaterials : synthetic biology‐derived molecular tools and design concepts are transferred to materials sciences for the synthesis of information‐processing materials systems. This concept is demonstrated by the implementation of a biohybrid materials system able to count the number of input light pulses. Synthetic biology‐inspired smart materials systems can provide novel solutions as integrated sensors and actuators.